2005
DOI: 10.1177/002204260503500209
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Marijuana use over the Transition into Marriage

Abstract: Reductions in substance use tend to coincide with marriage, as both may occur during emerging adulthood. During the transition to marriage, it is possible that one's spouse may be the influence that causes the reduction in substance use. Data on participants (N = 471 couples) for this report are taken from a longitudinal study of early marriage. The objective of the current analysis is to determine if having a spouse who uses marijuana is associated with a greater likelihood of one's own use. Additionally, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…To adapt to this changing pattern of socializing, some individuals may change their substance use patterns in response to their partner's drinking. Other research has found that spousal influence across a variety of substances is quite strong in the early years of marriage (e.g., Leonard and Homish, 2005;Leonard and Mudar, 2003). Those individuals whose drinking does not initially match or become more similar with their partners may be more likely to engage in other activities independent of their spouse.…”
Section: Discussionmentioning
confidence: 99%
“…To adapt to this changing pattern of socializing, some individuals may change their substance use patterns in response to their partner's drinking. Other research has found that spousal influence across a variety of substances is quite strong in the early years of marriage (e.g., Leonard and Homish, 2005;Leonard and Mudar, 2003). Those individuals whose drinking does not initially match or become more similar with their partners may be more likely to engage in other activities independent of their spouse.…”
Section: Discussionmentioning
confidence: 99%
“…Marriage tends to be associated with lower substance use and abuse. For instance, marriage is negatively related to marijuana use, especially if the spouse does not use marijuana (Leonard and Homish 2005;Yamaguchi and Kandel 1985). Marriage is also negatively related to alcohol use (Chilcoat and Breslau 1996) and problem drinking (Horwitz and White 1991;Horwitz et al 1996a;Karlamangla et al 2006).…”
Section: Work and Economic Conditions Family Roles And Substance Usmentioning
confidence: 99%
“…However, few studies have been conducted examining predictors of marijuana use cessation among teens (37) and young adults (812). The purpose of the current study was to apply a theoretical framework to the prediction of marijuana use cessation at 1-year follow-up among a sample of adolescents attending alternative high schools who were regular users at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Social and interpersonal variables are those that operate within the subject’s social environment, generally as reported by the subject, and influence one’s perceptions of one’s social world. Participation in adult social roles (e.g., marriage, being a parent) (7, 912), less peer use and approval (59), less victimization (5), and using marijuana for social reasons (4, 9, 11) have also been associated with marijuana use cessation among youth and young adults.…”
Section: Introductionmentioning
confidence: 99%